A prospective study of adverse drug reactions in a tertiary care teaching hospital - Daulat, More Pankaj; V. J., Ambika Abhishake; Singh, Prabhakar; Raj, Bhupendra (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Adverse drug reactions (ADRs) have become frequent cause for hospitalization and are coming up as an economic burden on health systems. Identification of ADRs and their reporting pattern can provide useful information for their management. Methods: This was an observational and prospective study. ADR reports of 130 patients were collected of the inpatient department of various clinical departments of Sanjay Gandhi Memorial Hospital, Rewa, Madhya Pradesh (M.P.) The ADRs were collected during October 2014-September 2015, with ADR reporting form of Central Drugs Standard Control Organization (CDSCO), New Delhi. ADRs were assessed for their causality, severity, and preventability as per the standard scales. Data was analysed using descriptive statistics and expresses in percentages. Results: Overall occurrence of ADRs was slightly more in males (55%). Maximum (26%) suspected ADR reported during study period was skin rash. Skin (44%) was the most commonly affected organ system. Antimicrobials (68%) were the drug group most commonly involved in ADRs. Most of the suspected ADRs were probable in causality assessment, moderate in severity and probably preventable. Conclusions: The study results revealed opportunities for interventions in ADR management to ensure safer drug use.